Prevalence and Predictors of Persistent Human Immunodeficiency Virus Viremia and Viral Rebound After Universal Test and Treat: A Population-Based Study. (20th January 2021) - Grabowski, M Kate; Patel, Eshan U; Nakigozi, Gertrude; Ssempijja, Victor; Ssekubugu, Robert; Ssekasanvu, Joseph; Ndyanabo, Anthony; Kigozi, Godfrey; Nalugoda, Fred; Gray, Ronald H; Kalibbala, Sarah; Serwadda, David M; et al.
Abstract: Background: There are limited data on individual human immunodeficiency virus (HIV) viral load (VL) trajectories at the population-level after the introduction of universal test and treat (UTT) in sub-Saharan Africa. Methods: Human immunodeficiency virus VLs were assessed among HIV-positive participants through 3 population-based surveys in 4 Ugandan fishing communities surveyed between November 2011 and August 2017. The unit of analysis was a visit-pair (2 consecutive person-visits), which were categorized as exhibiting durable VL suppression, new/renewed VL suppression, viral rebound, or persistent viremia. Adjusted relative risks (adjRRs) and 95% confidence intervals (CIs) of persistent viremia were estimated using multivariate Poisson regression. Results: There were 1346 HIV-positive participants (n = 1883 visit-pairs). The population-level prevalence of durable VL suppression increased from 29.7% to 67.9% during UTT rollout, viral rebound declined from 4.4% to 2.7%, and persistent viremia declined from 20.8% to 13.3%. Younger age (15–29 vs 40–49 years; adjRR = 1.80; 95% CI = 1.19–2.71), male sex (adjRR = 2.09, 95% CI = 1.47–2.95), never being married (vs currently married; adjRR = 1.88, 95% CI = 1.34–2.62), and recent migration to the community (vs long-term resident; adjRR = 1.91, 95% CI = 1.34–2.73) were factors associated with persistent viremia. Conclusions: Despite increases in durable VL suppression during roll out of UTT in hyperendemic communities, a substantial fraction of the population, whose risk profile tended to be younger, male, and mobile, remained persistently viremic. Abstract : This population-based study assessed longitudinal patterns in HIV viral load suppression after universal treatment in Uganda and observed increases in durable suppression; however, those with viremia were largely persistently viremic and more likely to be young, unmarried, male, and mobile.